2016
DOI: 10.1513/annalsats.201507-446oc
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Erector Spinae Muscles in Patients with Chronic Obstructive Pulmonary Disease. Novel Chest Computed Tomography–derived Index for Prognosis

Abstract: ESMCSA assessed by chest CT may be a valuable clinical parameter, as ESACSA correlates significantly with physiological parameters, symptoms, and disease prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
185
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(197 citation statements)
references
References 33 publications
9
185
2
1
Order By: Relevance
“…The presence of significant relationships between functional parameters and longitudinal PaO 2 trajectories in patients with COPD is one of the novel findings from the present study. Moreover, these results are consistent with our report showing that diffusing capacity is a significant prognostic factor in male patients with stable COPD, 20 and that emphysema severity, which is closely associated with diffusing capacity, is a significant prognostic factor identified in numerous cohort studies, including our previous study. 21 Our findings suggest that patients with a low K CO should be closely observed and undergo serial assessments of physiological parameters, including PaO 2 .…”
Section: Discussionsupporting
confidence: 93%
“…The presence of significant relationships between functional parameters and longitudinal PaO 2 trajectories in patients with COPD is one of the novel findings from the present study. Moreover, these results are consistent with our report showing that diffusing capacity is a significant prognostic factor in male patients with stable COPD, 20 and that emphysema severity, which is closely associated with diffusing capacity, is a significant prognostic factor identified in numerous cohort studies, including our previous study. 21 Our findings suggest that patients with a low K CO should be closely observed and undergo serial assessments of physiological parameters, including PaO 2 .…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, most cystic fibrosis patients were not age‐matched with this older control group. Also, it is unknown whether severe lung disease alters the geometry of the thoracic cavity, which could lead to differences in thoracic muscle CSA attributable to variation in the distribution of the thoracic muscles rather than muscle atrophy . However, in a previous study, we observed that a single thoracic axial CT slice was closely associated with thoracic muscle volume obtained from several slices in lung transplant candidates .…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, in lung transplant patients, muscle CSA from abdominal CT has been associated with post‐transplant outcomes such as intensive care unit (ICU) and hospital length of stay . In patients with chronic obstructive pulmonary disease (COPD), muscle CSA from chest CT has been associated with disease severity , exercise capacity , and mortality . We have recently shown that measures of thoracic muscle CSA from a single axial slice of the chest correlated well with accepted measures of muscle mass and were reproducible in lung transplant candidates .…”
Section: Introductionmentioning
confidence: 97%
“…Sarcopenia is prevalent in COPD, and is an independent risk factor for comorbidities and poor prognosis . In addition, our recent cohort study showed that the cross‐sectional area of antigravity muscle on chest computed tomography would represent a good prognostic index for COPD and might be associated with the physical activity level …”
Section: Introductionmentioning
confidence: 92%
“…13,14 In addition, our recent cohort study showed that the cross-sectional area of antigravity muscle on chest computed tomography would represent a good prognostic index for COPD and might be associated with the physical activity level. 15 The linkage among reduced muscle mass, physical inactivity and pulmonary dysfunction represents an important key feature of aged COPD patients. In addition, because COPD is a debilitating disease, malnutrition is also important for COPD patients.…”
Section: Introductionmentioning
confidence: 99%